Inhibition of VEGF signaling pathway attenuates hemorrhage after tPA treatment - Kanazawa, Masato (Nature Publishing Group, 2011)
An angiogenic factor, vascular endothelial growth factor (VEGF), might be associated with the blood–brain barrier (BBB) disruption after focal cerebral ischemia; however, it remains unknown whether hemorrhagic transformation (HT) after tissue plasminogen activator (tPA) treatment is related to the activation of VEGF signaling pathway in BBB. Here, we hypothesized that inhibition of VEGF signaling pathway can attenuate HT after tPA treatment. Rats subjected to thromboembolic focal cerebral ischemia were assigned to a permanent ischemia group and groups treated with tPA at 1 or 4 hours after ischemia. Anti-VEGF neutralizing antibody or control antibody was administered simultaneously with tPA. At 24 hours after ischemia, we evaluated the effects of the antibody on the VEGF expression, matrix metalloproteinase-9 (MMP-9) activation, degradation of BBB components, and HT. Delayed tPA treatment at 4 hours after ischemia promoted expression of VEGF in BBB, MMP-9 activation, degradation of BBB components, and HT. Compared with tPA and control antibody, combination treatment with tPA and the anti-VEGF neutralizing antibody significantly attenuated VEGF expression in BBB, MMP-9 activation, degradation of BBB components, and HT. It also improved motor outcome and mortality. Inhibition of VEGF signaling pathway may be a promising therapeutic strategy for attenuating HT after tPA treatment.